THE RELATIONSHIP ON THE LEVEL KNOWLEDGE OF NURSES AMONG PATIENT SAFETY IMPLEMENTATION IN EMERGENCY ROOM AND INTENSIVE ROOM AT LEUWILIANG HOSPITAL BOGOR: HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PELAKSANAAN KESELAMATAN PASIEN (PATIENT SAFETY) DI IGD DAN ICU RSUD LEUWILIANG KABUPATEN BOGOR - Chuchum Chuchum Sumiarty (Wijaya Husada, 2018)
Patient safety is a hospital service system that provides patient care more safely. It can be said that the main focus of patient safety is the effort taken to avoid mistakes. This study aims to determine the knowing the correlation between the level of knowledge of nurses and the implementation of patient safety in Emegency room and Intesive room at Leuwiliang Hospital, Bogor in 2018. The type of research used is analytic with cross sectional approach. The population of this study is nurses who work in the emergency room and ICU. Respondents of this study were all nurses who collected samples by using the Non Random Sampling method, namely Purposive sampling. The instrument used in this study is a questionnaire that discusses knowledge and 25 questions for patients. The analysis is chi square. The results of the study obtained from 33 respondents as many as 12 (36.4%) nurses who had insufficient knowledge to implement Patient Safety according to the Standard Operating Procedure. Based on the statistical test with chi square obtained a significant value of 0.053 (p> 0.05) this shows that Ha is rejected and Ho is accepted. It can be concluded that there is a relationship between the level of knowledge of nurses and the implementation of patient safety in Emergency and Intensive room of Leuwiliang Hospital, Bogor in 2018. This research is expected to be an evaluation material for Leuwiliang Hospital, Bogor, as well as an additional reference for Institute of Health Science Wijaya Husada and for the further researcher.